2016
DOI: 10.1016/j.ijggc.2015.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of relative permeability–saturation–capillary pressure models for simulation of reservoir CO2 injection

Abstract: the S k r  relations are obtained by fitting to experimental data using either an 10 endpoint power law or a modified Corey approach. The six models were tested 11 using data from four well-characterized sandstones (Berea, Paaratte, Tuscaloosa, 12Mt. Simon) for two radial injection test cases. The results show a large variation 13 in plume extent and saturation distribution for each of the sandstones, 14 depending on the used model. The VG-Mualem model predicts plumes that are 15 considerably larger than for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 57 publications
0
19
0
Order By: Relevance
“…We used linear relative permeability and capillary pressure models in these simulations. It has long been recognized that relative permeability and capillary pressure models influence plume migration . While the metrics presented here can help investigate this issue, this is beyond the scope of the current paper.…”
Section: Development Of Metrics To Describe Evolution Of Complex Plumesmentioning
confidence: 99%
See 1 more Smart Citation
“…We used linear relative permeability and capillary pressure models in these simulations. It has long been recognized that relative permeability and capillary pressure models influence plume migration . While the metrics presented here can help investigate this issue, this is beyond the scope of the current paper.…”
Section: Development Of Metrics To Describe Evolution Of Complex Plumesmentioning
confidence: 99%
“…It has long been recognized that relative permeability and capillary pressure models influence plume migration. [23][24][25] While the metrics presented here can help investigate this issue, this is beyond the scope of the current paper. The mesh is composed of 201 by 201 cells in the horizontal direction and 11 cells in the vertical direction (444,411 50 × 50 × 10 m cells).…”
Section: Example Applications Of Plume Mobility Metricsmentioning
confidence: 99%
“…The simulations have been used for estimating CO2 injectivity, CO2 plume extent, pressure distribution, thermal impact of the injection, and for the design of CO2 injection operations. They are detailed in several papers by Nguyen et al (submitted), Oostrom et al (2016), White et al (submitted), and Zhang et al (2015Zhang et al ( , 2016.…”
Section: Modeling Of Co2 Injection and Transportmentioning
confidence: 99%
“…Some unique aspects of mechanisms involved in the underground displacement of injected CO 2 for high permeability zones have been addressed in the literature. Oostrom et al . qualitatively studied the influence of relative permeability on CO 2 plume distribution and observed that for high permeability zones, the influence of relative permeability on plume shape is not as significant as is in lower permeability zones.…”
Section: Introductionmentioning
confidence: 99%
“…Some unique aspects of mechanisms involved in the underground displacement of injected CO 2 for high permeability zones have been addressed in the literature. Oostrom et al 3 qualitatively studied the influence of relative permeability on CO 2 plume distribution and observed that for high permeability zones, the influence of relative permeability on plume shape is not as significant as is in lower permeability zones. Mathias et al 4 also studied the effect of uncertainty in relative permeability data on CO 2 injectivity in brine formations and showed that uncertainty in the relative permeability data should be captured in simulations to have a reasonable representation of the system under consideration.…”
Section: Introductionmentioning
confidence: 99%